GENERA COMPOSITION OF BETHYLIDAE (HYMENOPTERA, CHRYSIDOIDEA) FROM EASTERN URUGUAY (Boletín de la Sociedad Zoológica del Uruguay, 2022)
The flat wasps Bethylidae are the largest family of Chrysidoidea. Because of their undeniable ecological contribution, these insects are also important due to their potential use as biological controllers of Coleoptera and Lepidoptera that act as agricultural pests. This is the first study focused on the diversity of Bethylidae in Uruguay and the attempt to get to know the Bethylidae fauna of this country. They were collected from three environments, natural field area (NFA), pasture system area (PSA), integrated livestock production system with winter and summer agriculture (IAAa and IAAb) near Castillos, Rocha Department, Uruguay, between December 2014 and December 2016. A total of 682 bethylids were collected, representing four subfamilies and 13 genera, of which one subfamily (Scleroderminae) and eight genera (Nothepyris, Plastanoxus, Cephalonomia, Allobethylus, Aspidepyris, Chlorepyris, Laelius and Dracunesia) were first registered for Uruguay.
Keywords: flat wasps; Neotropical; parasitoid wasps; South America